Monte Carlo simulation of 6 MV flattening filter free photon beam of TrueBeam STx LINAC at Songklanagarind Hospital - M. Arif Efendi,; Amporn Funsian,; Thawat Chittrakarn,; Tripob Bhongsuwan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this study, 6 MV photon beam of TrueBeam STx Varian LINAC with Flattening Filter Free (FFF) was simulated using PRIMO code. The depth dose profiles for various jaws open fields and cross beam profiles for various depths inside water phantom were determined using Monte Carlo (MC) simulation technique and validated with experimental result. The experiments were performed using the Source to Surface Distance (SSD) technique with a 100 cm distance from target to the surface of water. Simulation used 109 histories with the same configurations with experiments. The depth dose profiles and cross beam profiles of 6 MV FFF photon beam was determined using MC simulations and compared with experimental results. The results showed that depth dose profiles and cross beam profiles by MC simulation accurately matched with experimental results. The best result of depth dose profile was obtained at 10×10 cm2 jaws open field with 98.53% passing criterion whereas cross beam profile was obtained at 10 cm depth inside water phantom with 88.96% passing criterion.The discrepancies were caused by scatter of particle and incompatibility of primary beam in PRIMO with experiment.